The Outcome on Conservative Surgical Treatment of Adenomyosis - Wiweko, Budi; Legiantuko, Ario; Kemal, Achmad; Pratama, Gita; Situmorang, Herbert; Sumapraja, Kanadi; Natadisastra, Muharam; Hestiantoro, Andon (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To understand the outcome on conservative surgical treatment of adenomyosis. Methods: A retrospective cohort study followed for 2 years from 2010 to 2012 of women with adenomyosis were diagnosed by transvaginal sonography and confirmed histologically. Subjects divided into women who were treated by adenomyosis resection (with/without Osada’s technique) and who were underwent hysterectomy. Results: After the surgery, as many as 40 patients (81.63%) did not feel any pain (VAS 0), and 9 patients (18.37%) still felt pain. For the fertility outcome, we had 8 patients (20.51%) getting pregnant naturally without any fertility intervention. Two patients (5.13%) had successfully conceived by IVF. According to the type of surgery, from 8 natural pregnancy, 7 patients (87.50%) was underwent conventional resection of adenomyosis and 1 patients (12.50%) underwent Osada’s procedures. Two patients who were conceived by IVF, both of them were underwent Osada’s resection. Conclusion: Adenomyosis resection both conservative or Osada’s procedures actually has a better outcome for relieving pain; therefore, some patients can still have a child. Keywords: adenomyosis resection, conventional resection, infertility, Osada’s procedure